Assessment of Malaysian ICU staff perceptions towards STAR glycaemic control protocol - Abdul Razak, Athirah; Abu-Samah, Asma; Abdul Razak, Normy Norfiza; Baharudin, Saliza; Mohamad Suhaimi, Fatanah; Jamaludin, Ummu Kulthum; Md Ralib, Azrina; Mat Nor, Mohd Basri; Pretty, Christopher G. (Institute of Electrical and Electronics Engineers Inc., 2019)
A good glycaemic control protocol requires an assessment feedback from clinical side for improvement to reduce dysglycaemia (hyper or hypo) and most importantly mortality in critically ill patients. This includes medical doctors and nurses' perceptions on glycaemic control protocol clinical feasibility where a good protocol needs to be simple, effective, efficient and safe to be used on critically ill patients in the intensive care unit. This paper assessed medical doctors and nurses' perceptions on the implementation of Stochastic Targeted (STAR) glycaemia control protocol pilot trial through survey questions. Medical doctors and nurses at International Islamic University Malaysia Medical Centre (IIUMMC) were given 13 questions to investigate their perceptions of STAR protocol monitoring and patient's outcome. The results survey is important for sustainability of a good blood glucose management and prolonged used of STAR protocol. The results of this survey showed that 50% of the participants found that STAR protocol is easy to be used, 62.5% agreed on its performance with low risk and 87.5% approved that STAR protocol improves patient's outcome. In conclusion, the survey results showed that the staff are favorable towards STAR control to replace the usage of sliding scale protocol for glycaemic control in their ICU.